Weak Digital Literacy of Junior High School Students in Receiving Information on Social Media - Aas Ariska; Aqila Zahra Kamila; Keisha Alifa Miliana; Seli Cahya Sumirat; Yusticia Lex Divina; Ahmad Fuadin (CV. Rayyan Dwi Bharata, 2023)
Society has experienced changes in all forms of life. Technology has become an inseparable part of society. All people in society can already use technology in this day and age. One of the goals of people from various circles using technology is because of their curiosity about information that can be accessed easily on the internet. The majority of internet users in Indonesia are teenagers who are in junior high school (SMP) and high school (SMA). Therefore it is necessary to understand wisely how to use the internet. Today, there are many cases of spreading hoaxes that affect the mindset of internet users. Literacy is also needed to be implemented in adolescents when using digital media, especially on social media. Achievements in this literacy activity can encourage and influence adolescent perceptions of consumption of information media in the form of digital media so as to change adolescent beliefs and behavior. Do not let internet users, especially junior high school students, believe all forms of information circulating on the internet.